2016
DOI: 10.1002/jbio.201500331
|View full text |Cite
|
Sign up to set email alerts
|

Endoluminal application of glass-capped diffuser for ex vivo endovenous photocoagulation

Abstract: Endovenous laser ablation (EVLA) has frequently been used to treat varicose veins for 20 years. In spite of 90˜95% occlusion rates, clinical complications such as burn and ecchymosis still occur due to excessive thermal injury to perivenous tissue. In the current study, a glass-capped diffusing applicator is designed to validate the feasibility of EVLA as an effective therapeutic device by applying circumferential light distribution. The proposed device is evaluated with a flat fiber as a reference in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Although the optical diffuser was developed to deliver laser light radially to treat urethral stricture, the previous study pointed out that out‐of‐center phenomena occurred due to blind deployment of the optical diffuser, irregular urethral structure and lack of centering methods . In addition, various types of fiber tips such bare flat fiber, Tulip‐Tip, NeverTouch, radial fiber and diffusing fiber were used for endovenous laser ablation for treatment of varicose veins . Nonetheless, without any geometric restraints to prevent the fibers from making contact with vein wall, perforations often occur primarily due to overheating from unfavorable tissue contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the optical diffuser was developed to deliver laser light radially to treat urethral stricture, the previous study pointed out that out‐of‐center phenomena occurred due to blind deployment of the optical diffuser, irregular urethral structure and lack of centering methods . In addition, various types of fiber tips such bare flat fiber, Tulip‐Tip, NeverTouch, radial fiber and diffusing fiber were used for endovenous laser ablation for treatment of varicose veins . Nonetheless, without any geometric restraints to prevent the fibers from making contact with vein wall, perforations often occur primarily due to overheating from unfavorable tissue contact.…”
Section: Discussionmentioning
confidence: 99%
“…A number of laser types have been effectively and efficiently used such as Nd:YAG (1064 nm), thulium fiber laser (1940 nm), potassium‐titanyl‐phosphate (KTP, 532 nm) and CO 2 (10.6 μm) lasers . In particular, many scientists have been using optical diffusing fibers to either induce stricture or treat stenosis in tubular tissue such as varicose veins , urethra , seminal duct and trachea in rabbits . However, it is relatively difficult to insert and position the laser device at the right center of lumen to induce a circumferentially homogeneous coagulation in the tissue walls.…”
Section: Introductionmentioning
confidence: 99%
“…Cyindrical di®users (CD) are widely used in light therapies, such as photodynamic therapy, 18 photoimmunotherapy, 19 photothermal therapy, 20 and photocoagulation. 21 Kang et al proposed a catheter-based CD as a feasible therapeutic tool to photocoagulate endometrial cell layers in an e±cient and safe manner. 22 In previous work by our team, we proposed a PA method for the estimation and reconstruction of 3D light distribution produced by a CD in biological tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the radial light diffusion from the fabricated fiber entails irreversible tissue denaturation in the tubular tissue structure such as urethra [11]. Due to lower irradiance than the flat-cut fiber (i.e., 13.5 kW/cm 2 for diffuser vs. 64.9 kW/cm 2 for flat fiber), the diffuser reportedly generated up to 50% lower peak temperature and up to 90% thermal gradient in vein [12]. Histological analysis also confirmed that coagulative necrosis was consistently developed around the lumen within 1 mm [11].…”
Section: Introductionmentioning
confidence: 99%